Spell - Lauterbach, Ann 1942- (Penguin Books, 2018)
"A new collection of thought-provoking poems from the author of Or to Begin Again, a finalist for the 2009 National Book Award Ann Lauterbach is one of America's most innovative poets, acclaimed for her fierce, sensuous, and intellectually charged work. In her tenth collection, Spell, Lauterbach activates the many meanings of "spell": her sense that the world is under a possibly evil spell from which it must awaken, to the simple spells of changing weather, to her desire to spell out the difficulties and wonders of contemporary life. In short poems, poem sequences, and a meditative "Conversation with the Evening," Lauterbach calls upon all her imaginative resources to locate a new hybrid poetics of reality, with wit, urgency, and incisive candor"...
Keywords: POETRY / American / General / bisacsh; POETRY / American / General